ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DENGAN KUALITAS PELAYAN PADA TOKO SAMPOERNA DI SITUBONDO SEBAGAI VARIABEL MODERASI - Rahman, Ahmad Syaifur; Hamdun, Edy Kusnadi; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2024)
With the development in the current era of technology which is increasingly modern, it will make many businesses experience a high increase and progress, one of which is the development of the retail business. The purpose of this study was to analyze Product Prices, Location, Service Quality in influencing Purchasing Decisions at Sampoerna Stores in Situbondo. This research is explanatory research. The population in this study were consumers of Sampoerna Stores. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application, show that Price has a positive but insignificant effect on Purchasing Decisions, Location has a positive and significant effect on Purchasing Decisions, Price moderated by service quality has a positive but insignificant effect, Location moderated by service quality has a negative but insignificant effect.